2011
DOI: 10.1007/s00281-011-0297-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the host–pathogen interface for treatment of Staphylococcus aureus infection

Abstract: Recent emergence of methicillin-resistant Staphylococcus aureus both within and outside healthcare settings has accelerated the use of once reserved last line antibiotics such as vancomycin. With increased use of antibiotics, there has been a rapid rise in the rate of resistance development to the anti-MRSA drugs. As the antibiotic pipeline becomes strained, alternative strategies are being sought for future treatment of S. aureus. Here, we review several novel anti-staphylococcal strategies that, unlike conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 173 publications
0
19
0
1
Order By: Relevance
“…Some evidence suggests an association between bacterial strains which express Panton Valentine leukocidin (PVL) and severe complications, such as deep venous thrombosis and septic pulmonary emboli [5,7,27]. However, there is limited direct evidence of the role of single virulence determinants in the pathogenesis of virulent strains [37]. The redundancy of bacterial genes coding for leukocyte defense and the presence of PVL in non-virulent strains imply a more complex cascade of events than that which is explained by the activity of an isolated virulence gene [34,37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests an association between bacterial strains which express Panton Valentine leukocidin (PVL) and severe complications, such as deep venous thrombosis and septic pulmonary emboli [5,7,27]. However, there is limited direct evidence of the role of single virulence determinants in the pathogenesis of virulent strains [37]. The redundancy of bacterial genes coding for leukocyte defense and the presence of PVL in non-virulent strains imply a more complex cascade of events than that which is explained by the activity of an isolated virulence gene [34,37].…”
Section: Resultsmentioning
confidence: 99%
“…However, there is limited direct evidence of the role of single virulence determinants in the pathogenesis of virulent strains [37]. The redundancy of bacterial genes coding for leukocyte defense and the presence of PVL in non-virulent strains imply a more complex cascade of events than that which is explained by the activity of an isolated virulence gene [34,37]. In support of this, one group of investigators evaluated 33 putative virulence factors in bacterial isolates from individuals with either invasive or non-invasive S .…”
Section: Resultsmentioning
confidence: 99%
“…ue to the widespread and seemingly inevitable development of bacterial resistance to antibiotics shortly after their introduction, there is a great need for alternatives or adjuncts to classical antimicrobials (1)(2)(3). Along with ongoing efforts to identify novel antibacterial targets, interventions that are not directly bactericidal may prove efficacious.…”
mentioning
confidence: 99%
“…Along with ongoing efforts to identify novel antibacterial targets, interventions that are not directly bactericidal may prove efficacious. These include approaches aimed at modifying or augmenting the host response, as well as approaches that inhibit bacterial virulence mechanisms and thus limit pathogenesis (1)(2)(3). Many pathogenic bacteria coordinate the expression of virulence factors important for invasive infection and pathogenesis through a density-dependent communication system called quorum sensing (QS) (4,5).…”
mentioning
confidence: 99%
“…S. aureus is the most common pathogen responsible for both acute and chronic forms of osteomyelitis (1,5,6). S. aureus has developed a plethora of strategies to evade the host innate and adaptive immune systems, with a high resistance to different therapeutic options (7). Tice et al in a long-term follow-up study of osteomyelitis treated in the outpatient setting found that 31% of 452 patients had recurrent infection, most within one year of occurrence (8).…”
Section: Introductionmentioning
confidence: 99%